Straightforward and sensitive detection of micro-nano plastics with surface-enhanced Raman spectroscopy by the filtration-dissolution- adsorption strategy - Hao Liu; Hui Liang; Siyuan Zheng; Rui Hu; Wenqiang Pei; Le Wang; Yongchao Lai (Sensors and Actuators Reports)
Micro-nano plastics (MNPs) have become pervasive throughout the environment and emerged as significant pollutants, posing a potential threat to the natural environment and human health. Nonetheless, there remains a technological gap in the accurate analysis of trace and small-size MNPs in the environment. This study proposes a refined strategy for sample pretreatment and surface-enhanced Raman spectroscopy (SERS) analysis of MNPs in a water environment. MNPs were initially captured from the matrix using filter membranes, and subsequently released using an appropriate solvent. This approach not only separated the MNPs from the matrix and impurities, but also allowed the irregular and rigid MNPs to fit the surface of the KI-modified SERS substrates. This SERS-based approach facilitates the analysis of polystyrene (PS) MNPs of varying sizes at a concentration of 0.05 ng/mL across multiple water matrices. Furthermore, PS MNPs released from disposable cups were found using this method in everyday life. This simple and highly efficient strategy is ideal for the analyzing MNPs in everyday life and has the potential to facilitate future research on MNPs in the environment and their impact on human health.